Evolution of Cost Allocation Systems. Implementation ABC methods by Icelandic companies - Solodovnychenko,Victoría, 1967- (2013)
The purpose of the current study was to describe the evolution of cost allocation systems from the simplest ones to the most complex – integrated cost allocation system, which use financial and non-financial information to evaluate organizational performance. Then, apply theories into practice by research and analysis of cost allocation systems in the use by Icelandic companies. The first chapter introduces cost accounting and management accounting, and how these disciplines developed over the time. Inclusive is a short overview of the history of cost accounting from the dawn of civilization to the present time. The main emphasis was on the development of modern theories, methodologies and practices. Based on academic literature and publications about cost accounting and management accounting were described four-stage model for designing cost and performance measurement systems. Special attention was paid to activity-based cost methodology and systems. In the second chapter were described the research of what types of cost allocation systems are used by companies operating in Iceland. In scope of this research, companies were divided into three groups by their size: small, medium and large-sized companies. Cost allocation systems were observed and examined. The examination sought to establish the links between theories of different designs of cost allocation systems from the first part of the thesis, and general companies’ practices. The chapter closes with the overview of findings and possible proposed solutions.